Mycoplasma sp. infection in captive Marcgrave's capuchin monkeys (Sapajus flavius). (April 2017) - Ramalho, Ayodhya C.; Guerra, Ricardo R.; Mongruel, Anna C.B.; Vidotto, Odilon; Lucena, Ricardo B.; Guerra, Monalisa V.S.F.; Vieira, Thállitha S.W.J.; Vieira, Rafael F.C.
Highlights: A potential novel Mycoplasma sp. was detected in 66.7% of the critically endangered Marcgrave's capuchin monkeys ( Sapajus flavius ) from Brazil. Hemoplasma species has been placed in the ' Ca. M. haemomacaque' clade, within M. haemofelis group, in Maximum Likelihood phylogenetic tree. Only 1/8 (12.5%) hemoplasma-positive monkey was anemic. Clinical signs and the main vector remain unknown. Active surveillance programs are crucial for monitoring animal health status, particularly in critically endangered wild species. Abstract: Three species of hemoplasmas are known to infect monkeys, ' Candidatus Mycoplasma kahanei', ' Candidatus Mycoplasma haemomacaque' and ' Candidatus Mycoplasma aoti'. Marcgrave's capuchin monkey ( Sapajus flavius ) is a critically endangered neotropical primate species of the Brazilian Atlantic Forest, and thus, sustained efforts are needed to protect the health and well-being of these animals. This study has aimed to screen 12 captive S. flavius from the State of Paraíba, northeastern Brazil, for hemoplasma infection. Packed cell volume (PCV) was measured and a pan-hemoplasma PCR protocol performed. A total of 8/12 (66.6%) monkeys were positive for the 16S rDNA gene of Mycoplasma sp., showing an identity of 99% to Mycoplasma sp. previously detected in Sapajus apella and Sapajus sp. monkeys from the Brazilian Amazon. Further studies should be conducted in order to elucidate whether this potentially novel Mycoplasma sp. is able to cause anemia in Sapajus sp. monkeys from Brazil.